2021
DOI: 10.1111/zph.12818
|View full text |Cite
|
Sign up to set email alerts
|

Genomic features and antimicrobial resistance patterns of Shiga toxin‐producing Escherichia coli strains isolated from food in Chile

Abstract: Shiga toxin-producing Escherichia coli (STEC) is a zoonotic pathogen that causes severe illness in humans, often associated with foodborne outbreaks. Antimicrobial resistance among foodborne E. coli has increased over the last decades becoming a public health issue. In this study, the presence and features of STEC were investigated in samples of meat, seafood, vegetables and ready-to-eat street-vended food collected in Chile, using a genomic and microbiological approach. Phenotypic and genotypic antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 85 publications
(112 reference statements)
0
11
1
Order By: Relevance
“…Recent reports in Chile indicate STEC positivity rates of 17% in cattle and 1% in slaughtered pigs [48]. In addition, reports on meat, seafood, vegetables and ready-toeat street-vended food samples indicate 0.5% positivity (18/3300) [77]. However, the results obtained for STEC in this study are the first reported at BPS level in Chile.…”
Section: Stec and S Enterica Positivity In Bpscontrasting
confidence: 51%
“…Recent reports in Chile indicate STEC positivity rates of 17% in cattle and 1% in slaughtered pigs [48]. In addition, reports on meat, seafood, vegetables and ready-toeat street-vended food samples indicate 0.5% positivity (18/3300) [77]. However, the results obtained for STEC in this study are the first reported at BPS level in Chile.…”
Section: Stec and S Enterica Positivity In Bpscontrasting
confidence: 51%
“…The stx subtype most frequently detected was stx2a (54.6%, n = 71), followed by stx1a (26.9%, n = 35), stx2c (22.3%, n = 29), stx2d (16.2%, n = 21), stx2b and stx2g (1.5%, n = 2), and stx1c (0.8%, n = 1). Among the other virulence genes assessed, the most frequently detected was ehaA (96.2%, n = 125), followed by iha Studies focusing on the AMR of STEC strains isolated from the livestock-beef-human interface in South America are scarce [38,41,[61][62][63]. In this study, genomic analysis revealed a low prevalence of resistance genes.…”
Section: Virulome and Antibiotic Resistome Of Stec Strainsmentioning
confidence: 61%
“…Serotypes O157:H7 and O113:H21 have been the most frequently detected in cattle, beef, other foodstuffs, and humans in South American countries [19,55,61,[84][85][86]. In silico analysis confirmed that 96.3% of the O157:H7 strains were isolated in Argentina from beef and human clinical samples, while all O113:H21 strains were isolated in Chile from beef and cattle samples, suggesting selection and predominance of specific serotypes within each country.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations